SPECIAL ARTICLE COVID-19: ENT Manifestations in Patients Suffering from COVID- 19: Study from a COVID Hospital in North India - Srivastava,Anitya (2022)
Abstract Introduction COVID-19 has been one of the worst pandemics faced by the human civilization, and otorhinolaryngological manifestations are commonly seen in this disease. Objective The present study was done to profile the ear, nose, and throat (ENT) manifestations in patients diagnosed with COVID-19. An attempt has also been made to assess whether there was any difference between the symptoms of different strains of COVID-19. A brief review of the current knowledge of the transmission of the disease and its treatment has also been done. Methods A cross-sectional, record-based study was conducted in a COVID hospital of India between May and July 2020. Descriptive statistics were used and appropriate parametric/nonparametric tests were applied to assess the association between various variables. Results Out of 250 patients, 80 cases were asymptomatic and 170 were symptomatic. Most of the symptomatic patients had sore throat and nasal congestion. Conclusion Knowledge of the ENT manifestations of COVID-19 is essential for its early identification and to devise appropriate prevention protocols for the benefit of health care workers (HCWs) and of the general population.